Fostering critical thinking skills in ESL reading comprehension through SOLO questions / Mohd Sirhajwan Idek - Idek, Mohd Sirhajwan (2020)
There is still an apparent lack of critical thinking skills in English language reading comprehension among Malaysian secondary school students. This has been a major issue in the rural area of Sabah, the most isolated state of Malaysia. The students lacked the necessary skills to analyze reading texts to attain deep understanding as they became accustomed to recalling and recognizing skills only. Thus, the goal of this research is to examine the feasibility of SOLO (Structured of Observed Learning Outcomes) Taxonomy as the framework for designing questions that could foster higher order thinking skills in English as Second Language (ESL) reading comprehension. Questions are the most common tool used by any teacher in the classroom to elicit students’ responses and to evaluate their understanding but this research focused on utilizing questions to deepen students’ understanding of what they read by getting them to respond to questions which were developed according to SOLO levels: unistructural, multistructural, relational and extended abstract. The subject consisted of 30 students from two intact classes in a vocational secondary school located in the rural area of Sabah. This study narrowed the focus on four reading comprehension strategies: prediction, inference, questioning and making connection. An eight-week intervention that utilized SOLO questions in reading comprehension task was conducted to identify any possible effect of this approach. The mixed methods study comprised of pretests and posttests, questionnaire, interviews and concept maps. The results recorded students’ improved performance in utilizing the reading comprehension strategies that demonstrated their abilities to think more critically. It was also discovered that the students needed more support to progress from multistructural level to relational level as they struggled to balance consistency and closure. They were either reluctant to go beyond the text in order to remain consistent or they attempted to reach closure without sufficient explanation. Thus, the major implication of this study is the need to maximize multistructural level by getting students to familiarize themselves with the process of generating and ideas and exploring multiple ideas. Another implication is the importance of making them aware of their own thinking process so they learn to connect ideas in a meaningful manner that lead to well-supported conclusions. It is recommended that the role of lower level of understanding especially multistructural level in getting students to reach higher order thinking to be examined and explored as such responses might serve as early positive signs of critical thinking skills.